COVID-19: A Window of Opportunity for Positive Healthcare Reforms - Stefan Auener; Danielle Kroon; Erik Wackers; Simone van Dulmen; Patrick Jeurissen (Kerman University of Medical Sciences, 2020)
The current coronavirus disease 2019 (COVID-19) pandemic is testing healthcare systems like never before and all efforts are now being put into controlling the COVID-19 crisis. We witness increasing morbidity, delivery systems that sometimes are on the brink of collapse, and some shameless rent seeking. However, besides all the challenges, there are also possibilities that are opening up. In this perspective, we focus on lessons from COVID-19 to increase the sustainability of health systems. If we catch the opportunities, the crisis might very well be a policy window for positive reforms. We describe the positive opportunities that the COVID-19 crisis has opened to reduce the sources of waste for our health systems: failures of care delivery, failures of care coordination, overtreatment or low-value care, administrative complexity, pricing failures and fraud and abuse. We argue that current events can canalize some very needy reforms to make our systems more sustainable. As always, political policy windows are temporarily open, and so swift action is needed, otherwise the opportunity will pass and the vested interests will come back to pursue their own agendas. Professionals can play a key role in this as well.